Tailored Surface Wettability of Gas Diffusion Layer in Polymer Electrolyte Membrane Fuel Cells: Proposing a Pore Scale‐Two Phase Design. Issue 6 (28th September 2018) - Nazari, M.; Shakerinejad, E.; Kayhani, M. H.
Abstract: In this study, lattice Boltzmann method (LBM) is used to investigate liquid water transport in a gas diffusion layer (GDL) of polymer electrolyte membrane fuel cells (PEMFC) by considering mixed wettability. The GDL is reconstructed using the stochastic method and the simulations are performed to explore liquid water behaviors in the GDL. In this study, the dynamic behavior of liquid water during removal from gas diffusion layer of a PEMFC electrode is analyzed. The results are related to the water management and the optimal design of the GDL. The effects of inserted hydrophilic layer on the removal process and water distribution are investigated and a wettability‐tailored GDL is proposed. In addition, liquid water dynamic behaviors and liquid water saturation within the GDL in steady state and transient mode are explored. The effects of mixed wettability on the effective clusters in GDL, merging of different clusters and the loops developed by the fingers are investigated in detail. The optimum thickness and optimum location for the inserted hydrophilic layer inside the GDL are also proposed. The results show that combination of hydrophilic layer with the hydrophobic pores leads to an increase in the performance of the PEMFCs. In other words, the water management in GDL can be suitably done by selection of location and thickness of inserted hydrophilic layer. Regarding different test cases, the optimum location of the inserted hydrophilic layer is GDL‐GC interface with the optimum thickness of 12.5% of GDL thickness.